Implementasi Model Spatial Autoregressive dalam menentukan faktor-faktor yang mempengaruhi indeks pembangunan manusia di Kabupaten/Kota Provinsi Sumatera Barat - Febriani, Puja (UNIVERSITAS NEGERI PADANG, 2025)
The human development index (HDI) indicates the quality of human life in a region. The purpose of this study is to create a HDI model using a Spatial Autoregressive Model (SAR) and to determine the significant factors influencing HDI. This type of research is applied research. The data used are secondary data from publications by the Central Bureau of Statistics of West Sumatra Province in 2023. The method used in this study is SAR. The research results show that the SAR model formed for the HDI in the i-th District/City of West Sumatra Province in the year 2023 is and that the factors that significantly affect the human development index in the districts/cities of West Sumatra Province are life expectancy, years of schooling, and per capita expenditure.